Study of the structure of the thylakoid membrane-bound chloroplast coupling factor CF1 - Malyan, A N; Vitseva, O I; Strotmann, H (Biochemistry (Moscow), 1999)
The structure of thylakoid membrane-bound chloroplast coupling factor CF1 was studied by limited proteolysis followed by sodium dodecylsulfate polyacrylamide gel electrophoresis and N-terminal sequence analysis. The N-terminal fragment of the alpha-subunit was shown to have an exposed area including the peptide bond R21-E22. The cleavage of this peptide bond caused the alphaK24-V25 bond to be exposed to the outside. In the N-terminal fragment of the beta-subunit, the L14-E15 bond was identified and found to be subject to trypsinolysis. Also, the alphaR140-S141, alphaG160-R161, and betaG102-G103 bonds were accessible to the proteolytic attack. In general, the beta-subunit of membrane-bound CF1 is more sensitive to proteolysis than that of solubilized CF1. The products of proteolysis of the alpha-subunit did not contain the polypeptides typical of the reaction of cleavage of the alphaE17-G18 and alphaE22-V23 bonds in isolated CF1. These results suggest a significant structural difference between soluble and membrane-bound CF1. A number of peptide bonds, alphaG160-R161 in particular, were shown to be shielded from proteolytic attack by papain in illuminated thylakoid membranes, probably as a result of membrane energization. In contrast, the light-induced reduction of the gamma-subunit caused an increase in the accessibility of some peptide bonds to this protease, including the alphaG160-R161 bond.